The Impact of Augmented Reality Media on IPAS Learning Outcomes: A Moderated Analysis of Learning Motivation - Septi Misliza; Anisah; Yeni Erita; Muhammadi (Postgraduate, University of Mataram, 2025)
Student learning achievement is influenced by the quality of instructional media, yet IPAS learning outcomes in several elementary schools remain low due to limited media variation. This study aimed to analyze the effects of Augmented Reality (AR)–based media, learning motivation, and their interaction on fourth-grade students’ IPAS learning outcomes. A quantitative experiment with a 2×2 factorial design was conducted involving 43 students (22 in the experimental group and 21 in the control group). Learning motivation was categorized into high and low levels using a motivation questionnaire administered prior to treatment. Pre-test and post-test instruments were used to measure learning outcomes. Data were analyzed using a two-way ANOVA after meeting normality and homogeneity assumptions, with Mann–Whitney U tests performed only as complementary pairwise comparisons. The results showed a significant main effect of AR-based media on learning outcomes (p = 0.002) and a significant main effect of learning motivation, where high-motivation students achieved higher scores than low-motivation students (p = 0.023 and p = 0.027). However, the interaction between AR media and learning motivation was not significant, indicating that AR media improved outcomes regardless of students’ motivation level. In conclusion, AR-based media effectively enhance IPAS learning outcomes, although their impact is not influenced by motivation.